Evaluation of disinfectants used in pre-chilling water tanks of poultry processing plants - Guastalli, B. H.L. [UNESP]; Batista, D. F.A. [UNESP]; Souza, A. I.S. [UNESP]; Guastalli, E. A.L.; Lopes, P. D. [UNESP]; Almeida, A. M. [UNESP]; Prette, N.; Barbosa, F. O. [UNESP]; Stipp, D. T.; de Freitas Neto, Oliveiro Caetano [UNESP] (FapUNIFESP (SciELO), 2016)
In poultry processing plants, disinfectants are often added to prechilling water tanks to reduce microbial contamination. The present study aimed at evaluating the effect of five disinfectants (acidified sodium chlorite, alkyl dimethyl benzyl ammonium chloride, chlorine dioxide, peracetic acid, and sodium hypochlorite) on the populations of food quality indicator microorganisms and on Salmonella Enteritidis (SE) in the presence and absence of organic matter. The results showed that chlorine dioxide and sodium hypochlorite did not reduce microbial carcass counts. On the other hand, acidified sodium chlorite, alkyl dimethyl benzyl ammonium chloride and peracetic acid reduced total and fecal coliform counts. Peracetic acid reduced the number of psychrotrophic microorganisms. All products were effective in reducing SE counts only in the absence of organic matter. Acidified sodium chlorite, alkyl dimethyl benzyl ammonium chloride and peracetic acid could be candidates for the replacement of sodium hypochlorite (commonly used in Brazil) in pre-chilling tanks.
Keywords: Broiler carcasses; Disinfectant; Indicator microorganisms; Pre-chilling tank; Salmonella enteritidis